A Atypical presentation of Charcot-Marie-Tooth disease (CMT 2) with self mutilation of tongue as an early sign. A case report: CMT 2 in children - valasingam, Sandeep; lakshmi Madhuri; Rajesh Ninchenametla; Kranti Praveen (Journal of Orofacial Research, 2022)
Charcot-Marie-Tooth disease Axonal type (CMT 2) in children is usually diagnosed in the first decade of life with distal muscular atrophy and loss of sensitivity in the extremities. The present case report describes the early sensory involvement in an infant presented as frequent mutilation of the tongue. This report highlights the importance of considering progressive neuropathies as a differential when a dentist encounters self inflicting mutilation of the oral structures other than congenital insensitivity to pain.